(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
Fennel is a culinary spice of the Apiaceae family and is traditionally used as medicine for a wide range of ailments accompanied by digestive, respiratory, gastrointestinal and hormonal imbalance systems. Fennel has an anti-inflammation property to relieve normal cough/cold and abdominal pain. This research was assessed to analyse the chemical composition and biological activities in hexane and methanol extract of fennel seeds collected from the Terai region in the Uttarakhand state. Chemical composition was examined in polar (methanol) and non-polar (hexane) extracts of fennel seeds using GC-MS technique. An in vitro anti-diabetic and anti-inflammatory assay was observed in fennel extract. A statistical approach was done by cluster analysis in fennel seeds. D-arabitol (29.51%), Octadecadienoic acid (25.80%), Methyl pyrrolidine (23.41%), Guanosine (15.73%), Xanthine riboside (16.10%) were major components identified in methanol extract of fennel. Octadecenoic acid, palmitic acid, oleamide, trimesic acid, and linoleic acid were observed to major in the range of 79.43, 12.61, 32.76, 17.66, and 35.18 in the hexane extract of fennel, respectively. The highest α-amylase and α-glucosidase inhibition potential were observed in the hexane extract of FNL-125 (IC50=227.77±0.64 μg/mL) and FNL-120 (IC50=230.02±0.62 μg/mL), respectively. Hexane extract of FNL-125 (IB50= 676.44±0.96 μg/mL) exhibits superior anti-inflammatory activity. These fennel seeds have effective biological activities in hexane extract, suggesting their use for drug purposes. A statistical approach was undertaken with cluster analysis in fennel seeds that could be used to develop a new variety of fennel that possesses prominent chemical constituents with effective pharmacological activities and to be used in pharma industries.